Nanoconjugation and Encapsulation Strategies for Improving Drug Delivery and Therapeutic Efficacy of Poorly Water-Soluble Drugs - Thao T. D. Tran; Phuong H. L. Tran (MDPI AG, 2019)
Nanoconjugations have been demonstrated to be a dominant strategy for drug delivery and biomedical applications. In this review, we intend to describe several strategies for drug formulation, especially to improve the bioavailability of poorly water-soluble molecules for future application in the therapy of numerous diseases. The context of current studies will give readers an overview of the conjugation strategies for fabricating nanoparticles, which have expanded from conjugated materials to the surface conjugation of nanovehicles. Moreover, nanoconjugates for theranostics are also discussed and highlighted. Overall, these state-of-the-art conjugation methods and these techniques and applications for nanoparticulate systems of poorly water-soluble drugs will inspire scientists to explore and discover more productive techniques and methodologies for drug development.